Spondweni virus causes fetal harm in Ifnar1(−/−) mice and is transmitted by Aedes aegypti mosquitoes - Jaeger, Anna S. (Virology, 2020)
Spondweni virus (SPONV) is the most closely related known flavivirus to Zika virus (ZIKV). Its pathogenic potential and vector specificity have not been well defined. SPONV has been found predominantly in Africa, but was recently detected in a pool of Culex quinquefasciatus mosquitoes in Haiti. Here we show that SPONV can cause significant fetal harm, including demise, comparable to ZIKV, in a mouse model of vertical transmission. Following maternal inoculation, we detected infectious SPONV in placentas and fetuses, along with significant fetal and placental histopathology, together suggesting vertical transmission. To test vector competence, we exposed Aedes aegypti and Culex quinquefasciatus mosquitoes to SPONV-infected bloodmeals. Aedes aegypti could efficiently transmit SPONV, whereas Culex quinquefasciatus could not. Our results suggest that SPONV has the same features that made ZIKV a public health risk.